Exploring Antioxidant Potential Of Crataeva Nurvala Leaves: A Comprehensive Pharmacognostic And Physicochemical Insight - Chandra Prakash Bhardwaj; Dr. Piush Sharma (Revista Electronica de Veterinaria, 2023)
Crataeva nurvala, a member of the Capparidaceae family, commonly known as Varuna, is a medium-sized, deciduous tree that is native to India and other parts of South Asia. Reaching heights of 5-10 meters, it features distinctive trifoliate leaves and fragrant white to yellow flowers that attract pollinators. Traditionally, various parts of Crataeva nurvala have been used in folk medicine for their potential health benefits, including metabolic disorders, anti-inflammatory and digestive properties, making it both ecologically and culturally significant. The present research includes a comprehensive pharmacognostic study, detailing the macroscopic and microscopic characteristics of the plant, which aids in its identification and authentication. Physicochemical analysis was also performed to determine moisture content, ash value, and extractive values, which are crucial for ensuring quality control and standardization. Antioxidant assays, including 2,2-Diphenyl-1-picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Power (FRAP), Nitric Oxide (NO), and Superoxide Radical Scavenging Activity (SRSA), were used to evaluate the plant’s free radical scavenging potential. Microscopic and fluorescence analyses further support quality control efforts. Ongoing research explores the therapeutic potential and safety of Crataeva nurvala. Different antioxidant activity assay methods, revealed that the leaf’s aqueous extract ACN has a better IC50 value than ECN in the DPPH, FRAP, and NO assays, indicating stronger antioxidant activity in these tests. ECN only outperforms ACN in the SRSA assay, but the difference is not substantial. ACN shows overall stronger antioxidant activity compared to ECN when considering all four assays. Therefore, ACN is the sample that shows the best antioxidant result compared to the standard (STD) across these assays. This comprehensive evaluation highlights the medicinal value of Crataeva nurvala, particularly in its antioxidant properties.